Neuromyopathy due to mitochondrial trifunctional protein deficiency caused by novel HADHA mutation - Vatkar, Amit; Joshi, Nishigandha; Patil, Smita; Shariff, Mumtaz (Indian Journal of Child Health, 2022)
Mitochondrial trifunctional protein deficiency (MTP deficiency or MTPD) is a rare autosomal recessive disorder of oxidation of long-chain fatty acids. It is characterized by severe neonatal manifestations such as cardiomyopathy, hypoglycemia, metabolic acidosis, skeletal myopathy, neuropathy, liver disease, and death. It can also present with mild symptoms such as peripheral polyneuropathy, episodic rhabdomyolysis, and pigmentary retinopathy. Peripheral neuropathy is a known and long-term irreversible complication of MTPD. We report a rare case of a 5-year-old male child with slowly progressive limb weakness; genetic analysis was suggestive of MTPD with novel HADHA gene mutation. The present study comprehensively analyzed the cases, including exome sequencing, to the best of our knowledge, describing the first observation of homozygous novel mutation in the HADHA gene underlying this disorder in India.